Hubungan Durasi dan Frekuensi Kuliah Daring Dengan Conference Fatigue Pada Mahasiswa Fakultas Kedokteran Universitas Nusa Cendana - Sibero, Peniel Peranta Reynaldi Tarigan; Ratu, Kristian; Nurina, Listyawati; Folamauk, Conrad L.H. (Universitas Nusa Cendana, 2022)
Background : The learning process during the pandemic outbreak in various educational institutions is very diverse. The online learning system is implemented using various types of videoconferencing applications. It is known that there are still many students who does not know the impact of conference fatigue when carrying out the online learning process.Objective: To analyze the correlation between the duration and frequency of online lectures with the incidence of conference fatigue among medical students at the University Nusa Cendana.Method : The research process is an observational analytic with a cross sectional design carried out on students of the Faculty of Medicine, University Nusa Cendana batch 2018, 2019, 2020, and 2021. Sampling was carried out using the simple random method and obtained as many as 137 respondents. Data were taken using an online lecture duration and frequency questionnaire and Zoom Exhaustion and Fatigue Scale (ZEF Scale) questionnaire which had been translated. Data were analyzed univariately and bivariately using the Pearson Correlation Test.Result : From 137 respondents, it was found that 51.8% of respondents experienced moderate level of conference fatigue, followed by 40.9% of respondents experienced low level of conference fatigue, the remaining 7.3% experienced high level of conference fatigue. Based on the results of the bivariate test, it was found that there was a significant relationship between the duration and frequency of online lectures on conference fatigue.Conclusion: There is a significant correlation between the duration and frequency of online lectures on conference fatigue among students of the Faculty of Medicine, University Nusa Cendana.